Endoscopy of GI Tract - Amornyotin, Somchai (IntechOpen, 2013)
Endoscopy has had a major impact in the development of modern gastroenterology and other medical specialties. The field of endoscopic procedure has developed over the last decade. By using different data it provided a better understanding of pathogenic mechanisms, described new entities and used for early detection, diagnostic procedures and therapeutic procedures. The advantages of many technical advances and modern-endoscopic equipments, endoscopy has had a developed spectacularly. Furthermore, endoscopy has surpassed its function as an examination tool and it became a rapid and efficient therapeutic tool of low invasiveness. The efficacy and usefulness of endoscopy has yet been established.